Implementation and indicator of limited face-to-face physical education in covid-19 - Fernanda Kustantri, Ocha; Rini Sukamti, Endang; Nanda, Fitri Agung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Learning carried out through limited face-to-face learning during the Covid-19 pandemic has been determined according to government regulations to increase the effectiveness of student learning in physical education learning. The purpose of this study was to find out how the implementation of physical education learning during the Limited Face To Face Physical Education (PTMT) period in the Covid-19 pandemic. The method used in this research is descriptive quantitative. The instrument was used through a questionnaire distributed to the sample, namely physical education teachers at SMPN Metro Lampung, totalling 26. The sample selection of the research was purposive technique because the sample was selected from schools that had already implemented limited face to face in physical education learning. The validity of the instrument with a validity value of 0.693, then the reliability value in this study was 0.935. The study results revealed that if the teaching hours applied by limited face to face physical education have reduced teaching hours. Then for infrastructure, indicators and learning applications are included in the sufficient category, and the best learning model used in limited face to face is individual learning. The results are expected to become a reference for the application of limited face to face physical education so that the results obtained are maximal.